2020
DOI: 10.1002/agg2.20055
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term rotation diversity and nitrogen effects on soil organic carbon and nitrogen stocks

Abstract: Understanding the impacts of long‐term fertilizer management and rotation diversity on soil C and N is needed under a changing climate. The objective of this study was to evaluate the effects of N fertilizer level and crop rotation diversity on soil organic carbon (SOC) and soil N stocks from a 34‐yr study located in eastern Nebraska. Seven crop rotations (three continuous cropping systems; two 2‐yr crop rotations; and two 4‐yr crop rotations) and three N levels were compared. Soil samples were taken to a dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…The benefits of CRD for crop performance under low and high precipitation are likely mostly mediated by changes to soil properties and ecosystem functioning. Increasing CRD could improve soil structure and soil organic matter content, facilitating the retention of water and nutrients in several field experiments (Kremen & Miles, 2012; Schmer et al., 2020; Sprunger et al., 2020). Nevertheless, trade‐offs might occur if the added crops increase water demands, as observed in some experiments (Blanchy et al., 2023), in the absence of sufficient soil water recharge outside the growing season.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of CRD for crop performance under low and high precipitation are likely mostly mediated by changes to soil properties and ecosystem functioning. Increasing CRD could improve soil structure and soil organic matter content, facilitating the retention of water and nutrients in several field experiments (Kremen & Miles, 2012; Schmer et al., 2020; Sprunger et al., 2020). Nevertheless, trade‐offs might occur if the added crops increase water demands, as observed in some experiments (Blanchy et al., 2023), in the absence of sufficient soil water recharge outside the growing season.…”
Section: Discussionmentioning
confidence: 99%
“…Results from present study also show that soybean-based crop rotation may reduce the SOC sequestration capacity of CA when compared to maize in NCP. However, most of the previous studies reported that: decomposition of crop residues could be accelerated by soybean compared to maize, and thus increase SOC content (Huggins et al, 2007;Schmer et al, 2020). The differences may be induced by the reduction of C input (King and Blesh, 2018) and the short experimental duration (Shrestha et al, 2013).…”
Section: Soc Storagementioning
confidence: 97%
“…Furthermore, the increase in the soil organic carbon in the agroecosystem with crop rotation system was due to the type of crops used in our study. Schmer et al (2020) found that significant soil organic carbon accretion in a 2-year and 4-year crop rotation compared to continuous cropping after 34 years can be attributed to the rotation complexity. The authors further noted that crops used in the rotation affects the residue mass and quality (i.e., carbon-nitrogen ratio) returned to the soil, which later contributes to the nitrogen immobilization.…”
Section: Impact Of Biobased Residues and Crop Rotation On Soil Organi...mentioning
confidence: 99%
“…Although the application rate of nitrogen fertilizer was lower compared to biobased residues, nutrient availability was highest for the fertilizer and lowest for the compost. This is because the compost had the highest carbon to nitrogen ratio, and lowest microbial carbon-use efficiency resulting in high soil organic carbon accumulation compared to nitrogen fertilizer (Schmer et al 2020;Badewa et al 2022). Manzoni et al (2012) observed that substrates with high carbon to nitrogen ratios, due to their nitrogen limitation, have a low microbial carbon-use efficiency.…”
Section: Carbon Nitrogen Turnover and Residue Stabilizationmentioning
confidence: 99%